2021
DOI: 10.1037/cfp0000148
|View full text |Cite
|
Sign up to set email alerts
|

Testing adaptations of cognitive-behavioral conjoint therapy for PTSD: A randomized controlled pilot study with veterans.

Abstract: Iraq and Afghanistan Veterans with posttraumatic stress disorder (PTSD) have welldocumented relationship problems and many wish to include their intimate partners in treatment. This pilot study randomly assigned 46 couples (Veterans with clinicianadministered PTSD scale confirmed PTSD diagnosis and their intimate partners) to one of two groups. The treatment group received a modified mindfulness-based version of cognitive-behavioral conjoint therapy for PTSD (CBCT; Monson & Fredman, 2012) that included all thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Finally, the dropout rate in the current study was high, although it is similar to previous studies of individual trauma‐focused treatment when dropout is defined in a similar way (Wierwille et al., 2016). Future research should continue to focus on strategies to enhance treatment retention, such as massed treatment delivered in a retreat format (Davis et al., 2021; Fredman et al., 2020) or abbreviated formats (Fredman et al., 2020; Morland et al., 2019), as couples who completed treatment experienced larger gains than those who dropped out. Future research can also expand upon using session‐level data to explore concurrent change in veterans’ and partners’ perceptions of veterans’ PTSD and both partners’ depression symptoms and relationship satisfaction while participating in CBCT for PTSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the dropout rate in the current study was high, although it is similar to previous studies of individual trauma‐focused treatment when dropout is defined in a similar way (Wierwille et al., 2016). Future research should continue to focus on strategies to enhance treatment retention, such as massed treatment delivered in a retreat format (Davis et al., 2021; Fredman et al., 2020) or abbreviated formats (Fredman et al., 2020; Morland et al., 2019), as couples who completed treatment experienced larger gains than those who dropped out. Future research can also expand upon using session‐level data to explore concurrent change in veterans’ and partners’ perceptions of veterans’ PTSD and both partners’ depression symptoms and relationship satisfaction while participating in CBCT for PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…(2020), increases in general relationship adjustment or satisfaction for one or both partners were also seen across studies, as were improvements in patient comorbid symptoms and partner mental health (i.e., depression, anxiety, anger). Improvements in PTSD symptoms and relationship functioning and decreases in partner accommodation have also been observed for several adaptations of CBCT for PTSD, including an abbreviated version delivered in multicouple groups over a single weekend (Fredman et al., 2020, 2021), a present‐focused version (Pukay‐Martin et al., 2015), and a mindfulness‐based version delivered in multicouple groups in a retreat format (Davis et al., 2021).…”
mentioning
confidence: 94%
“…A study examining the military‐to‐civilian transition of Australian Defense Force Veterans found that social connectedness was associated with better quality of life and reduced psychological distress (Flack & Kite, 2021). On a relational level, programs may prepare couples and families for changes that may occur in their life structure and relationship dynamic during the transition process (Davis et al, 2021). While the majority of participants stated that their command was supportive and understanding, some military leaders may need increased awareness of the stressors and support needed during the transition process.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several case studies have illustrated CBCT's diverse implementation with respect to relationship type (e.g., Blount et al, 2017) and nature of trauma exposure (e.g., Brown-Bowers et al, 2012). Recent studies specifically investigating adaptations of CBCT have also been promising, including a present-focused version of CBCT for PTSD that is geared toward individuals who are reluctant to participate in trauma-focused therapy (Pukay-Martin et al, 2017); an abbreviated, intensive, multicouple group version of CBCT for PTSD (Fredman et al, 2020(Fredman et al, , 2021; and versions of CBCT that have integrated components of behavioral couples therapy for alcohol use disorder (O'Farrell & Fals-Stewart, 2006;Schumm et al, 2015) and mindfulness (Davis et al, 2021;Luedtke et al, 2015). Taken together, research supports the adaptability of CBCT and suggests it is an effective and scalable treatment.…”
Section: Cognitive-behavioral Conjoint Therapymentioning
confidence: 99%